Loss and Renewal : Australian Languages Since Colonisation. - Meakins, Felicity (Language contact and bilingualism ;, 2016)
Australia is known for its linguistic diversity and extensive contact between languages. This edited volume is the first dedicated to language contact in Australia since colonisation, marking a new era of linguistic work, and contributing new data to theoretical discussions on contact languages and language contact processes. It provides explanations for contemporary contact processes in Australia and much-needed descriptions of contact languages, including pidgins, creoles, mixed languages, contact varieties of English, and restructured Indigenous languages. Analyses of complex and dynamic processes are informed by rich sociolinguistic description.